2015
DOI: 10.3109/0886022x.2015.1015390
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of ketamine and remifentanil on renal functions in coronary artery bypass graft surgery

Abstract: We have investigated the effects of ketamine-based and remifentanil-based anesthetic protocol on perioperative serum cystatin-C levels, and creatinine and/or cystatin-C-based eGFR equations in terms of acute kidney injury in coronary artery bypass graft (CABG) surgery. Using a simple randomization method (coin tossing), patients were divided into the two groups and not-blinded to the anesthetist. Remifentanil-midazolam-propofol or ketamine-midazolam-propofol-based anesthetic regimen was chosen. Different eGFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Studies that were not RCTs (n = 6), focused on surgical techniques or procedures (n = 23), or did not report the incidence of AKI-related outcomes or events (n = 28) were also excluded. Eight two-arm studies that could not connect to other studies in the network were also excluded (188)(189)(190)(191)(192)(193)(194). One study on the management of postoperative cardiogenic shock that compared vasopressin and norepinephrine, which was identified from a review article (6), was excluded for the same reason (195).…”
Section: Search Resultsmentioning
confidence: 99%
“…Studies that were not RCTs (n = 6), focused on surgical techniques or procedures (n = 23), or did not report the incidence of AKI-related outcomes or events (n = 28) were also excluded. Eight two-arm studies that could not connect to other studies in the network were also excluded (188)(189)(190)(191)(192)(193)(194). One study on the management of postoperative cardiogenic shock that compared vasopressin and norepinephrine, which was identified from a review article (6), was excluded for the same reason (195).…”
Section: Search Resultsmentioning
confidence: 99%
“…It has been reported that remifentanil and propofol itself, or combined with other drugs, may cause renal injury in healthy human patients [ 5 10 35 ]. Additionally, all pigs from all groups of our study were premedicated with azaperone, and this drug accumulates in pigs' kidneys and may also contribute to kidney damage [ 3 7 24 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…TUNEL method relies on the presence of nicks in the DNA which may be identified by terminal deoxynucleotidyl transferase [ 10 ]. The number of animals studied was six in each group.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, high sensitive cardiac troponin T is associated with renal insufficiency in patients with a myocardial infraction (Huang et al, 2015). GFR levels in these patients were quite low after surgery when anesthetized with ketamine (Demir et al, 2015). Ketamine abuse, in the form of drugs, is also reported for hydronephrosis (Abuse, Tran, Nelson, Nogar, & Bramante, 2014;Nickolas et al, 2008), cystitis (Ho et al, 2010), and urinary tract dysfunction (Mason, Cottrell, Corrigan, Gillatt, & Mitchelmore, 2010) perhaps, the consequence of the high concentration of ketamine metabolites like hydroxyl norketamines in the urine (Chu et al, 2008).…”
Section: Ketaminementioning
confidence: 99%
“…It targets N-methyl-D-aspartate receptors and shows inhibitory effects (Garcia, Kolesky, & Jenkins, 2010). Renal effects of ketamine in patients who underwent cardiac surgery showed a rise in urea, creatinine sCyC, and high sensitive troponin T levels, postoperatively (Demir et al, 2015). Besides this, high sensitive cardiac troponin T is associated with renal insufficiency in patients with a myocardial infraction (Huang et al, 2015).…”
Section: Ketaminementioning
confidence: 99%